Catalisadores heterogêneos à base de MoO3: influência da anisotropia e defeitos eletrônicos em reações de transesterificação para produção de biodiesel - Medeiros, Suelen Alves Silva Lucena de (2021)
Molybdenum trioxide is considered a versatile material due to its structural characteristics. It is generally found in the orthorhombic, monoclinic and hexagonal phase. Notably, the hexagonal and orthorhombic phases have received prominence in the most diverse field. In this work, the α-MoO3 and h-MoO3 phases were synthesized by the modified Pechini method, however, presenting two different route alternatives. Molybdenum trioxide orthorhombic phase was used as a heterogeneous catalyst in ethyl and methyl transesterification reactions for biodiesel production of soybean oil. The catalysts were characterized by the techniques: Thermogravimetry (TG), X-Ray Diffraction (XRD) at room temperature and hot camera, Dynamic light scattering (DLS), Infrared Spectroscopy (IR), Raman Spectroscopy, Spectroscopy in the region UV-Visible (UV VIS), Photoluminescence (FL), X-Ray Photoelectron Spectroscopy (XPS), Electron Paramagnetic Resonance Spectroscopy (EPR), Surface Area (BET) and Scanning Electron Microscopy (SEM). The diffractograms confirmed the achievement of the orthorhombic and hexagonal phases. From the diffractogram obtained in a hot camera, the transition from hexagonal-orthorhombic phase, around 370°C, was observed. As the calcination temperature increased, the α-MoO3 phase exposed an anisotropic growth of the planes (0 k 0). The micrographs of these hexagonal phase oxides exhibited morphologies in the form of hexagons, while the orthorhombic lamellar “tapes”, corroborating the structural organization. Through the quantification of total acid sites by n-butylamine, a greater amount was observed for the polycrystalline sample (500°C) compared to the oriented sample (700 ° C). This behavior was attributed to the stability of the surface (0 k 0) that reduces the adsorption process for materials calcined at 700°C. Species such as Mo5+ and Mo6+ were detected on the surface and bulk of these materials. The conversion into ethyl esters of 88% of the TEO_04 product was verified through the cromatography results, indicating the formation of biodiesel. The reuse tests showed a slight reduction in catalytic efficiency. The product obtained TMO50042 showed 98.48% conversion to methyl esters, a considerable result when compared to ANP parameters (RANP Nº 45/2014 NBR 15764).